NILAI-NILAI DAKWAH PADA PENCAK SILAT PERSAUDARAAN SETIA HATI TERATE (PSHT) KOMISARIAT UINSI SAMARINDA - Wihartati, Ayu; Bunyamin, Bunyamin; Salehuddin, Mohammad; Al-Mughni, Muhammad (Mushawwir Jurnal Manajemen Dakwah dan Filantropi Islam, 2023)
The implementation of PSHT Pencak Silat exercises apart from martial arts defends, attacks, or activities that hurt the body also has da'wah values ​​that instill discipline, honesty, hard work, spirituality, patience and decency. In the PSHT pecak silat, it is hoped that the teachings will maintain the best possible attitude wherever they are. Therefore, the purpose of the researcher is to find out the values ​​of da'wah that exist in PSHT Commissariat of UIN Sultan Aji Muhammad Idris Samarinda and how the application has been carried out until now. Results obtained from research. 1) It is important to instill discipline in PSHT members, because it reflects a good istiqamah spirit and not only applies discipline in terms of training but also in worship. 2) Honesty is applied with the hope that it will get used to and carry that attitude of honesty into everyday life, which can provide positive energy to those around it. 3) Hard work teaches us to understand that not everything can be achieved easily. 4) Spirituality with the aim of getting closer to God, so that students are formed into virtuous human beings. 5) Politeness with respect and mutual respect, speaking kind words. 6) Remain patient and sincere when what is expected does not go according to plan. Keywords: Da'wah values, PSHT, martial art